FRI0439 PET-CT IN THE ASSESSMENT OF OSTEOARTICULAR INFECTIONS ASSOCIATED WITH INFECTIVE ENDOCARDITIS. (2nd June 2020) - Hugues, B.; Emsen, B.; Ternacle, J.; Huguet, R.; Fiore, A.; Lepeule, R.; Chevalier, X.; Abulizi, M.; Eymard, F.
Abstract : Background: Five to eleven percent of infective endocarditis (IE) are associated with a musculoskeletal infection. Thanks to its good sensitivity, the use of PET-CT in this pathology makes it possible to confirm the diagnosis by seeking valvular hypermetabolism but also by mapping distant septic foci. Objectives: The main objective of our study was to assess the prevalence of osteoarticular fixation (OAF) with PET-CT, symptomatic or not, in patients with IE. The secondary objectives were to determine predictive factors for osteoarticular infections such as the type of valve damage (native or prosthetic) and germ. Methods: This study was carried out on the basis of a prospective cohort of patients admitted in the department of cardiology in Henri Mondor Hospital for IE suspicion between August 2015 and July 2019. Demographic, clinical, bacteriological, imaging and therapeutic data have been collected. Patients matching Duke's modified criteria according to ESC 2015 (Duke + IE) and / or a cardiac fixation according to standard whole-body PET-CT were included in the analysis. All of the PET-CT scans were reviewed by a nuclear medicine specialist to confirm whether or not there was a heart condition and to look for septic-looking OAF. Results: From this cohort, we included 90 IE Duke + patients and 42 patients with cardiac PET-CT fixation (including 31 IE Duke +). In the IE Duke + group, we found OAF in 18 patients (20%), 39% of whom were asymptomatic. There were 9 spondylodiscitis (4 on the cervical level, 7 on the thoracic level, and 2 on the lumbar level), 5 glenohumeral arthritis, 2 coxofemoral arthritis, 1 sternoclavicular arthritis and 1 sacroiliac arthritis. The IE affected the aortic valve in 50% of the cases and the mitral valve in 22%. In other cases, the infection involved the internal automatic defibrillator (ICD) or the pacemaker. The valves were prosthetic in 73% of the cases. The bacterial ecology was mainly represented by Enterococcus faecalis (39%) then staphylococcus aureus (17%) against 14% and 13% respectively in the entire IE Duke + group. In the group with cardiac PET-CT fixation, OAF was found in 10 patients (40%), 70% of whom were asymptomatic. Among them, there were 5 spondylodiscitis (2 cervico- thoracic and 3 exclusively thoracic), 2 glenohumeral arthritis (20%), 2 coxofemoral arthritis and 1 sternoclavicular arthritis. The IE affected the aortic valve in 60% of the cases, mitral in 30% of the cases and it was an infection on ICD in 10% of the cases. The main germs found were Enterococcus faecalis (30% of cases) and Staphylococcus epidermidis (20% of cases). Conclusion: In patients with IE, PET-CT seems to be interesting in detection of osteoarticular infections, and consequently, could impact the diagnosis and the treatment modalities. In our cohort, 1 patient in 5 had an OAF and nearly 40% of them were asymptomatic. The overrepresentation of enterococcus is consistent with recent data in the literature References: [1]Dahl A, Iversen K, Tonder N, Hoest N, Arpi M, Dalsgaard M, et al. Prevalence of Infective Endocarditis in Enterococcus faecalis Bacteremia. J Am Coll Cardiol. 16 juill 2019;74(2):193‑201. Disclosure of Interests: Benjamin HUGUES: None declared, Bérivan EMSEN: None declared, Julien TERNACLE: None declared, Raphaëlle HUGUET: None declared, Antonio FIORE: None declared, Raphaëlle LEPEULE: None declared, Xavier Chevalier: None declared, Mukedaisi ABULIZI: None declared, Florent Eymard Consultant of: Regenlab